METHOD OF CALCULATION OF PROTECTION OF INFORMATION AGAINST DISSEMINATION OF INFORMATION IN THE SOCIAL NETWORK - Divizinyuk, Michael; Akhramovich, Volodymyr; Lazarenko, Serhii; Dudnyk, Vladyslav; Yakoviv, Ivan (Ukrainian Information Security Research Journal, 2022)
In the modern world, there is a significant impact of social networks on all spheres of life of individuals and societies as a whole. Therefore, the problem of the protection of information and personal data in social networks is becoming increasingly important. To build systems for the protection of social networks, it is necessary to have quantitative indicators of the dependence of protection parameters on specific parameters of the network, including the parameters of information dissemination. At present, no studies have been identified that would provide an opportunity to assess these quantitative indicators. The solution to this problem is possible by modeling processes in social networks using a system of differential equations. The proposed method allows you to investigate whether the linear protection system, allows you to quantify the protection of the network from specific parameters, including the parameters of information dissemination.